Antioxidant Activity Testing of Extract Kweni Peel (Mangifera odorata Griff) - Yolanda Dwi Lestari; Suci Permatasari; Ade Oktasari (Universitas Negeri Yogyakarta, 2021)
This research aims to test the antioxidant activity of extract kweni peel (Mangifera odoratta Griff). The antioxidant testing was performed by maceration using the solvents of n-hexane and ethanol 96% after that it was fractioned using ethyl acetate solvent. The phytochemical tests yield positive results from ethyl acetate extract were flavonoids and tannins. The antioxidant testing was carried out using the DPPH method (2,2, diphenyl-1-picrylhydrazyl) based on the inhibition concentration test parameters (IC50). The result showed that the antioxidant activity (IC50) found to be 169.43 µg/mL which was classified as moderate antioxidant activity intensity. Therefore, it can be concluded that the extract of kweni peel (Mangifera odoratta Griff) has potential antioxidant activity that could be used as an inhibitor of free radicals.